PEMAHAMAN GURU SEKOLAH DASAR TERHADAP PENILAIAN BERBASIS HOTS DI KOTA PALEMBANG - Ela Okta Handini; Asnimar Asnimar; Laihat Laihat (Universitas Sriwijaya, 2020)
Teachers’ understanding is important in preparing assessment based on Higher Order Thingking Skills (HOTS) in elementary school learning in the city of Palembang. This research is a qualitative descriptive study. The research subjects were teachers who taught Grade VI Elementary Schools in Palembang, which amounted to 8 people. The research instrument used was a questionnaire. The results showed that the understanding of elementary school teachers in the city of Palembang was 71.87% in the good category. However, the teacher's understanding when differentiating between HOTS and not HOTS shows that the category is sufficient with 57.5% of teachers being able to distinguish between HOTS questions. Teachers still experience problems in preparing HOTS-based assessment instruments for learning in elementary schools that showed 78,125%. Based on the results of this study, it is necessary to develop guidelines for developing HOTS-based assessment instruments for learning in elementary schools.Keywords : Understanding, Assesment, HOTS